2005
DOI: 10.1095/biolreprod.104.037523
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Differentiation-Related Protein: A Gonadotropin- and Prostaglandin-Regulated Protein in Primate Periovulatory Follicles1

Abstract: The midcycle LH surge stimulates a rise in follicular fluid prostaglandin E2 (PGE2), which is necessary for normal ovulation. To examine PGE2-regulated processes in primate follicles, monkey granulosa cells were cultured with hCG alone or with hCG and PGE2, and the resulting total RNA was subjected to microarray analysis. Twenty PGE2-regulated mRNAs were identified, and we selected a lipid droplet protein, adipose differentiation-related protein (ADRP), for further study. To determine whether hCG and PGE2 regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 71 publications
4
33
0
Order By: Relevance
“…Plin2 and Plin3 are widely expressed in most cell types [31], [32]; Plin4 is found in white fat, skeletal muscle and the heart [33][35]; and Plin5 is found in the heart, brown fat, adipose tissue, liver, and skeletal muscle [32]. In our study, Plin2 appears to be the predominant Plin in granulosa cells (adipose differentiation-related protein, ADRP), which supports a previous finding of ADRP in primate granulosa cells [36]. A recent study demonstrated that different perilipin family members were found to preferentially associate with either TAG-enriched LDs or CE-enriched LDs [37].…”
Section: Discussionsupporting
confidence: 90%
“…Plin2 and Plin3 are widely expressed in most cell types [31], [32]; Plin4 is found in white fat, skeletal muscle and the heart [33][35]; and Plin5 is found in the heart, brown fat, adipose tissue, liver, and skeletal muscle [32]. In our study, Plin2 appears to be the predominant Plin in granulosa cells (adipose differentiation-related protein, ADRP), which supports a previous finding of ADRP in primate granulosa cells [36]. A recent study demonstrated that different perilipin family members were found to preferentially associate with either TAG-enriched LDs or CE-enriched LDs [37].…”
Section: Discussionsupporting
confidence: 90%
“…In a recent study from our group, PLIN2 was shown to be the predominant PLIN in granulosa cells (adipose differentiation-related protein, ADRP) (10), which confirms a previous finding of ADRP in primate granulosa cells (33). …”
Section: Ld Associated Proteins In Steroidogenic Tissuessupporting
confidence: 87%
“…We used hCG as a biochemical marker of cell differentiation. Recently, hCG was reported to induce ADRP mRNA and protein expression in granulosa cells, but it required the synergistic action of prostaglandin E 2 to do so (46). However, the increasing level of hCG could be part of the mechanism for ADRP induction during differentiation.…”
Section: Discussionmentioning
confidence: 99%